Enriching the stability of solar/wind DC microgrids using battery and superconducting magnetic energy storage based fuzzy logic control. (January 2022) - Kotb, Kotb M.; Elmorshedy, Mahmoud F.; Salama, Hossam S.; Dán, András
Highlights: Comparative analysis is presented for a PV/wind DC-bus MG integrating battery storage and SMES systems. A proposed FLC scheme is proposed for controlling both battery and SMES based on their actual currents. A variable modulation index control scheme is employed for the prime inverter for mitigating the load voltage/frequency. The control schemes are tested for regular and extreme variations of meteorological and loading instabilities. The SMES system shows a superior overall behavior over the battery during all examined fluctuations. Abstract: Utilizing robustly-controlled energy storage technologies performs a substantial role in improving the stability of standalone microgrids in terms of voltages and powers. The majority of investigations focused less on integrating energy storage systems (especially superconducting magnetic energy storage 'SMES') within DC-bus microgrids. Besides, implementing fuzzy logic control (FLC) for both batteries and SMES within the DC-bus microgrids to enrich their stability and power quality under extreme climatic and loading variations has been seldomly addressed. Consequently, this paper introduces a comparative analysis of the performance of a hybrid renewable PV/wind DC-bus microgrid that separately implements fuzzy-controlled battery and SMES systems to enhance the microgrid stability and power quality. The proposed FLC approaches supervise energy interchange inside the system, mitigate the DC-bus voltage fluctuations, and smooth out the load power during the different instabilities. The system is examined under distinct normal and extreme climatic fluctuations such as wind gusts and rapid shadow and under sudden balanced and unbalanced loading events. The proposed FLC approaches are established based on quantifying the DC-bus voltage variation and measuring the actual battery and SMES currents which can be employed directly for the control action; hence, reducing both calculations/calibrations and complexity of the control system. Besides, they offer very quick charging/discharging actions for both battery and SMES systems to mitigate unexpected and rapid variations efficiently. For the load side, the study proposes a variable modulation index control based-sinusoidal pulse width modulation for controlling the prime inverter to preserve the load voltage and frequency constant during both balanced and unbalanced loading and extreme climatic disturbances. The obtained findings confirmed the efficacy of the proposed approaches in enriching the microgrid stability. Besides, they unveiled the magnificent performance of SMES over batteries regarding the response time, peak over- and undershoot, load voltage profile, and load power smoothness.